2008
DOI: 10.1111/j.1600-065x.2008.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cell‐mediated immunity to the intracellular pathogen Francisella tularensis

Abstract: Summary Francisella tularensis can cause fatal respiratory tularemia in humans and animals and is increasingly being isolated in the US and several European countries. The correlates of protective immunity against this intracellular bacterium are not known and currently there are no licensed vaccines available for human use. Cell-mediated immunity has long been believed to be critical for protection and the importance of humoral immunity is also now recognized. Furthermore, synergy between antibodies, T cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
109
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 94 publications
6
109
0
2
Order By: Relevance
“…Cell-mediated immunity is generally considered to be essential for immunity against intracellular pathogens, and humoral immunity is thought to have more of an ancillary role. However, significant evidence in the literature indicates an important role of antibodies against F. tularensis LVS infection (13)(14)(15)(16)(17). Moreover, studies from our laboratory have recently reported a synergistic effect of humoral and cellular immune responses in providing sterilizing immunity against respiratory LVS infection (13).…”
Section: F Tularensis Lvs Infection Causes Significant Tissue Patholmentioning
confidence: 94%
“…Cell-mediated immunity is generally considered to be essential for immunity against intracellular pathogens, and humoral immunity is thought to have more of an ancillary role. However, significant evidence in the literature indicates an important role of antibodies against F. tularensis LVS infection (13)(14)(15)(16)(17). Moreover, studies from our laboratory have recently reported a synergistic effect of humoral and cellular immune responses in providing sterilizing immunity against respiratory LVS infection (13).…”
Section: F Tularensis Lvs Infection Causes Significant Tissue Patholmentioning
confidence: 94%
“…This is evident in murine models of tularemia, where robust proinflammatory responses are not observed during the first 48 to 72 h of infection (20)(21)(22)(23)(24). F. tularensis also dampens host-programmed cell death responses during infection (20,(25)(26)(27)(28)(29)(30)(31). Death of F. tularensis-infected cells occurs via two primary mechanisms: caspase-1-mediated pyroptosis and caspase-3-mediated apoptosis (25,32).…”
mentioning
confidence: 93%
“…IFN-␥-stimulated alveolar macrophages also secrete tumor necrosis factor alpha (TNF-␣); while it is not necessary for these cells to control F. tularensis LVS in vitro, it is required for protection in vivo (16). This suggests the involvement of other cell populations, possibly neutrophils, which are recruited to the lung within 3 days of F. tularensis infection (4,13).…”
mentioning
confidence: 99%
“…Macrophages significantly contribute to in vitro bacterial killing if they are stimulated with interferon gamma (IFN-␥) (2,(11)(12)(13). Correspondingly, IFN-␥ is known to be required for protection in vivo (14).…”
mentioning
confidence: 99%